Development of multiplex immuno-PCR diagnostic platform using chicken IgY antibodies for COVID-19 diagnosis - Altaha, Sondos; Al-Qaoud, Khaled; Al-Omari, Mariam; Al-Shawaheen, Aseel (The Journal of Infection in Developing Countries, 2025)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has significantly accelerated the development of diagnostic techniques. Real‑time quantitative polymerase chain reaction (RT‑qPCR) was the method of choice for diagnosis and was considered as the gold standard. However, limited specificity of RT-PCR was noticed during the pandemic. This research aimed to develop a combined highly specific immune-based and highly sensitive molecular-based diagnostic technique. Methodology: Groups of chicken were immunized with commercial severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) N, S, and E antigens. The IgY antibodies were purified from eggs using a High-Trap IgY affinity column. Three unique DNA barcodes were designed, synthesized, and amplified using 5′-amine–labeled forward primers. DNA barcodes purified form PCR products were coupled to IgY antibodies using the (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide) - N-hydroxysuccinimide (EDC-NHS) coupling chemistry. ELISA; SDS-PAGEs; immunoblot (IB); and uniplex-, duplex- and multiplex immuno-PCR (IPCR) were used to confirm system validity. Results: Amplification of single barcodes using RT-PCR showed a Ct value of 15, with no significant variation when amplified in duplex or multiplex formats. Chicken IgY–DNA barcode conjugation and reactivity were verified using IB and ELISA. IPCR resulted in efficient amplification of all three DNA barcodes in uniplex, duplex, and multiplex formats after binding to commercial N, S, and E antigens. Conclusions: The successful combination of the specific antibody-based techniques, low-cost chicken IgY antibodies, and RT-PCR sensitivity achieved in this study present a promising approach to meet the demand for sensitive and accurate diagnostics. This generic platform can be adopted in any analyte detection system.